A portable multi-modal micro-imaging system for automated scanning and image stitching applications : a thesis submitted to Massey University in accordance with the requirements of the degree of Master of Engineering in the School of Engineering and Advanced Technology - Naqvi, Adam (Massey University, 2019)
Microscopic imaging is an important element in many ﬁelds like biology, medicine, diagnostics, engineering, and materials research. Muti-modal microscopes are ideal for imaging samples that reveal unseen structures that could not otherwise be seen with normal bright-ﬁeld microscopes. Point-of-care micro-imaging devices are ones that can deliver the features of a microscope in areas where access to a laboratory or medical facilities are scarce. This thesis presents the development of a portable micro-imaging system that uses multi-modal illumination to image samples in bright-ﬁeld, ﬂuorescence, ambient and laser diffraction modes. A systematic design method has been used to develop the system from the conceptual phase to a working prototype. The system incorporates variable magniﬁcation through an inverted turret system and a GUI application for live image view, automatic scanning, auto-focusing and image processing. The utility of the system is demonstrated through imaging stained biological samples for a local industry application. The acquired images are measured against sharpness and noise. It is observed that the sharpness and noise of the images produced vary with the type of sample: samples with higher contrast generally produce sharper images with less noise. It has also been found that diffused ambient illumination produces the most consistent sharpness and noise scores between magniﬁcations. Performance of algorithms used is discussed and improvements are suggested for building a more compact and stable platform including a method to calibrate measurements for particle size estimation.
Figures are re-used with permission.
Keywords: Imaging systems; Design and construction; Microscopy; Point-of-care testing; 400304 Biomedical imaging